Interest Rate Policy and Investment Behavior: A Panel Dataset Analysis of Corporate Financial Decisions in Indonesia - Gladya Regita Siahaan; Patricia Aurel (Cv. Data Sinergi Digital, 2025)
This study investigates the effect of interest rate policy on corporate investment behavior using a panel dataset of non-financial firms listed on the Indonesia Stock Exchange (IDX) for the period 2015-2023. Drawing upon the neoclassical theory of investment, the financial accelerator framework, and the interest rate channel of monetary policy transmission, the research examines how changes in Bank Indonesia’s benchmark interest rate (BI-Rate) affect firm-level capital expenditure decisions. Using a balanced panel of 185 firms across nine sectors with 1,665 firm-year observations, the study employs fixed-effects and random-effects panel regression models, complemented by Generalized Method of Moments (GMM) estimation to address endogeneity. The dependent variable is the investment rate (capital expenditure scaled by lagged total assets), while independent variables include the BI-Rate, Tobin’s Q, cash flow-to-assets ratio, leverage, firm size, and GDP growth. The results reveal that an increase in the BI-Rate significantly reduces corporate investment, with a one-percentage-point rise associated with a 2.34 percentage-point decline in the average investment rate. The effect is heterogeneous: younger firms, highly leveraged firms, and firms in capital-intensive sectors exhibit greater sensitivity to interest rate changes, consistent with the financial accelerator hypothesis. Tobin’s Q and cash flow positively and significantly influence investment, while leverage exerts a negative effect. Robustness checks using two-step system GMM confirm the baseline findings. The study contributes to the literature by providing micro-level evidence on the monetary policy transmission mechanism in an emerging market context.